2010
DOI: 10.5194/angeo-28-1263-2010
|View full text |Cite
|
Sign up to set email alerts
|

The statistical properties of spread F observed at Hainan station during the declining period of the 23rd solar cycle

Abstract: Abstract. The temporal variations of the low latitude nighttime spread F (SF) observed by DPS-4 digisonde at low latitude Hainan station (geog. 19.5 • N, 109.1 • E, dip lat. 9.5 • N) during the declining solar cycle 23 from March 2002 to February 2008 are studied. The spread F measured by the digisonde were classified into four types, i.e., frequency SF (FSF), range SF (RSF), mixed SF (MSF), and strong range SF (SSF). The statistical results show that MSF and SSF are the outstanding irregularities in Hainan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
5
15
0
Order By: Relevance
“…We found that MSTIDs mainly appeared during the summer and propagated to the latitude region of Fuk near midnight. These two characteristics of MSTIDs are very consistent with those of the mixed spread F (MSF), previously reported by Wang et al [] at Fuk. Wang et al [] pointed out that the MSF at Fuk is also one of the main spread F types.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that MSTIDs mainly appeared during the summer and propagated to the latitude region of Fuk near midnight. These two characteristics of MSTIDs are very consistent with those of the mixed spread F (MSF), previously reported by Wang et al [] at Fuk. Wang et al [] pointed out that the MSF at Fuk is also one of the main spread F types.…”
Section: Discussionsupporting
confidence: 90%
“…The observed EPBs were usually generated in clusters (or groups) in broad longitudinal extensions of 250–3000 km, drifting eastward into the FOV of airglow imagers, digisonde, or scintillation monitors. The EPB seasonal occurrence pattern from the airglow images can be thus well compared with those based on digisonde and scintillation observations by Wang et al [] and Shi et al [].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…For instance, the issues in the equatorial ionosphere-thermosphere electrodynamics over American and Southeast Asia sectors (Abdu, 2001;Cabrera et al, 2010;Candido et al, 2011;Maruyama et al, 2007) or the investigations to find out the relation between the spread-F occurrence and the sporadic-E (Es) characteristics over the Brazilian conjugate point equatorial experiment (COPEX) (Batista et al, 2008). The statistics of spread-F occurrence over different regions confirm that at the different geomagnetic declinations, latitudinal and longitudinal regions, ESF occurrence and intensity have distinct annual or seasonal patterns (Abdu et al, 1981;Maruyama and Matuura, 1984;Sastri, 1999;Maruyama et al, 2002Maruyama et al, , 2007Saito and Maruyama, 2007;Wang et al, 2008Wang et al, , 2010Hoang et al, 2010;Amabayo et al, 2011;Pezzopane et al, 2013).…”
Section: Introductionmentioning
confidence: 68%
“…Besides, the variations of ESF were investigated as a function of geophysical indices such as the estimated planetary K-index (Kp), the disturbance storm time index (Dst), which indicate the level of magnetic activity or the geomagnetic storm, or the sunspot number (SSN), the F10.7 index, which indicate the level of solar activity. The characteristics and the occurrence rates of each ESF type differ according to the different levels of solar activity and seasonal variation (Abdu et al, 1998;Wang et al, 2008Wang et al, , 2010Amabayo et al, 2011). The spread-F occurrences are continuously investigated in various regions to ascertain the hypothesis of ESF characteristics and occurrences.…”
Section: Introductionmentioning
confidence: 99%